Species Delimitation, Phylogenetic Relationships, and Temporal Divergence Model in the Genus Aeromonas - Lorén, J. G.; Farfán, Maribel; Fusté, M. C. (Frontiers in Microbiology, 2018)
The definition of species boundaries constitutes an important challenge in biodiversity studies. In this work we applied the Generalized Mixed Yule Coalescent (GMYC) method, which determines a divergence threshold to delimit species in a phylogenetic tree. Based on the tree branching pattern, the analysis fixes the transition threshold between speciation and the coalescent process associated with the intra-species diversification. This approach has been widely used to delineate eukaryote species and establish their diversification process from sequence data. Nevertheless, there are few examples in which this analysis has been applied to a bacterial population. Although the GMYC method was originally designed to assume a constant (Yule) model of diversification at between-species level, it was later evaluated simulating other conditions. Our aim was therefore to determine the species delineation in Aeromonas using the GMYC method and asses which model best explains the speciation process in this bacterial genus. The application of the GMYC method allowed us to clearly delineate the Aeromonas species boundaries, even in the controversial groups, such as the A. veronii or A. media species complexes.